SARS-CoV-2-INDUCED MICROSCOPIC POLYANGIITIS: CLINICAL PROBLEM - Olga O. Gutsalenko; Borys M. Fylenko; Tetyana I. Yarmola; Nataliia V. Roiko; Iryna V. Tsyganenko (Клінічна та профілактична медицина, 2025)
Introduction. During the COVID-19 pandemic, the diagnosis and treatment of ANCA-associated vasculitis (AAV) have been discussed in different ways. At the same time, the authors of many foreign publications state that SARS-CoV-2 infection can be another viral trigger for the development of AAV in children and adults.